Romberg′s Syndrome - Masuria B. L; Jain V. K; Kothiwala R. K (Indian Journal of Dermatology, 1999)
A 16 year old female with facial hemiatrophy and convulsions having sparse right eyebrows and eye lashes, flattening of the nasolabial fold, protrusion of eye ball, and retraction of angle of mouth towards the affected side is reported.